Effect of talc on the properties of polypropylene/ethylene/propylene/diene terpolymer blends - Oksuz, Mustafa; Eroglu, Mehmet; Yildirim, Huseyin (Wiley, 2006)
In the present study, the effect of talc content on the mechanical, thermal, and microstructural properties of the isotactic polypropylene (i-PP) and elastomeric ethylene/propylene/diene terpolymer (EPDM) blends were investigated. In the experimental study, five different talc concentrations, 3 6, 9, 12, and 15 wt %, were added to i-PP/EPDM (88/12) blends to produce ternary composites. The mechanical properties such as yield and tensile strengths, elongation at break, elasticity modulus, izod impact strength for notch tip radius of 1 mm, and hardness with and without heat treatments and thermal properties, such as melt flow index (MFI), of the ternary composites have been investigated. The annealing heat treatment was carried out at 100 C for holding time of 75 h. From the tensile test results, an increased trend for the yield and tensile strengths and elasticity modulus was seen for lower talc contents while elongation at break showed a sharp decrease with the addition of talc. In the case of MFI, talc addition decreased the MFI of i-PP/EPDM blends. It was concluded that, taking into consideration, mechanical properties and annealing heat treatment, heat treatment has much more effect on higher yield and tensile strengths, elongation at break, elasticity modulus, impact strength, and hardness. (c) 2006 Wiley Periodicals, Inc.
Keywords: poly(propylene) (PP); talc; EPDM; mechanical properties; heat treatment